Kinetics Of The Oxidation Of Free And Copper Cyanides In Aqueous Solutions With Hydrogen Peroxide - Alexandre Bonan (The Minerals, Metals and Materials Society, 1994)
This paper reports the results of a kinetic study on the oxidation of free cyanide and Cu-cyanide complex ions with HO,. The variables and respective ranges studied were the following: [CN] total =10 - 500 mg/l; pH=10-11; (H2O2/CN) mole ratio = 1- 3; (Cu/CN) mole ratio = 0.10 - 0.25. The results were interpreted by a semi-empirical model that incorporates the useful oxidation reactions and the parallel alkaline decomposition of H2O2